EFFECT OF COMBINING LOSARTAN AND PERINDOPRIL IN DIABETIC PATIENTS WITH PROTEINURIA - Chin, Shin-chee; Md Redzuan, Adyani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This retrospective study compared the efficacy and safety of losartan monotherapy versus losartan and perindopril combination therapy in diabetic patients with hypertension and albuminuria. Factors affecting the change in albuminuria were identified. Methods: Through quota sampling, the study recruited patients from a tertiary care hospital. Outcome parameters included urinary albumin creatinine ratio (UACR), blood pressure (BP), serum creatinine, and estimated glomerular filtration rate (eGFR). Both pre- and post-treatment measurements were traced from patient's medical records. Results: No significant differences (p=0.615) were detected in the pre- and post-treatment change in UACR between the monotherapy group (âˆ’38.3 mg/g, interquartile range [IQR]:âˆ’618.8-0) and combination therapy group (âˆ’88.4 mg/g, IQR: âˆ’729.3-+375.7). There was a considerably higher percentage of patients attaining the target BP of <125/75 mmHg in the combination group (66.7%; p<0.001). In terms of safety, combined losartan and perindopril caused more hypotension (p=0.003), higher rise in serum creatinine (p=0.481), and greater drop in eGFR (p=0.861). Body mass index was shown to have significant negative correlation with UACR reduction (r=âˆ’0.449; p=0.036). Conclusion: The main finding of this study was that losartan alone was as equally efficacious as combined losartan and perindopril in lowering UACR and BP among diabetic patients. Â